Maszyny parowe w zbiorach Muzeum Historii Przemysłu w Opatówku pozyskane z zakładów przemysłowych w majątkach ziemskich - Dolat, Jarosław (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
Museum of history of industry piles antiques of industrial techniques in Opatówek. Documenting of history of industry is purpose of this activity, mainly industrial center kaliskie. It win objects be within the confines of this activity in terrestrial properties endowment of mill. Steam machines are these valuable antiques. First, dates from 1873 year from distillery of property firm “h” presenting ownership family “Paucksch und Freund” Lewków Lipski family. Second dates from 1886 year from property firm “&” Christoph Unmack AG Niesky OL Stropieszyn, there be ownership Celiński. Omit contribution in industrialization of country this investment considering not manner exactly gentry. So, these machines present examples of taking up by representatives to personal properties this group of investment. Certainly < obvious > boost of revenue was this purpose. If necessary it characterize presentations of these machines feature of local gentry.